2010
DOI: 10.1634/theoncologist.2009-0016
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma (Olfactory Neuroblastoma) with Ectopic ACTH Syndrome: A Multidisciplinary Case Presentation from the Joan Karnell Cancer Center of Pennsylvania Hospital

Abstract: The case of a patient with recurrent esthesioneuroblastoma complicated by ectopic adrenocorticotropic hormone production is presented, including the workup and management of this uncommon complication of an uncommon disease. The Oncologist 2010;15: 51-58 CASE PRESENTATIONIn 1992, a 55-year-old white man presented with epistaxis and was diagnosed with esthesioneuroblastoma. He underwent a craniofacial resection with postoperative radiation therapy to his tumor site. In 1996, he relapsed in the cervical lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Most of the 8 reported cases of ectopic ACTH were from primary ENB tumors. It has also been found to first appear with recurrent disease, as in one pediatric case of late cervical lymph node recurrence [41] and in two adult cases of local recurrence despite aggressive surgical management [42, 48]. Although one patient died of recurrent disease, treatment of the ENB and/or recurrence led to resolution of the associated Cushing's syndrome in all other cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the 8 reported cases of ectopic ACTH were from primary ENB tumors. It has also been found to first appear with recurrent disease, as in one pediatric case of late cervical lymph node recurrence [41] and in two adult cases of local recurrence despite aggressive surgical management [42, 48]. Although one patient died of recurrent disease, treatment of the ENB and/or recurrence led to resolution of the associated Cushing's syndrome in all other cases.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms at presentation are nasal obstruction, epistaxis, and anosmia. Rare patients have presented with production of ectopic adrenocorticotropic hormone (ACTH) and inappropriate secretion of antidiuretic hormone secretion [27,28]. A complete physical and radiological examination-including CT and MRI-are essential for diagnosis, staging, and proper treatment planning [10].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…There are previous reports describing secreting esthesioneuroblastomas, but few reports describing catecholamine‐producing esthesioneuroblastomas . Other studies have reported secretion of adrenocorticotropic hormone from esthesioneuroblastomas . Syndrome of inappropriate antidiuretic hormone has also been reported in patients with esthesioneuroblastoma , …”
Section: Discussionmentioning
confidence: 99%